Sodium-ion battery negative electrode material and preparation method and application thereof
By introducing defects and small active molecules on the surface of the negative electrode material of the sodium ion battery, a carbon negative electrode material modified with topological defects was prepared, which solved the problem of poor universality of the modification method in the prior art and significantly improved the electrochemical performance of the sodium ion battery.
Patent Information
- Application Number
- CN202411688456.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-25
Smart Images

Figure CN119569111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and more specifically to a sodium ion battery negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, the continuous development of large-scale industry, electric vehicles, and portable electronic devices has put forward higher requirements for the performance of energy storage devices. Lithium-ion batteries have the advantages of high energy density and long cycle life, and are the main power source for equipment in the above fields. Sodium resources are widely distributed in the earth's crust and are low-cost. Emerging sodium-ion batteries have begun to emerge in the field of electrochemical energy storage as a low-cost alternative to lithium-ion batteries. However, the diffusion rate of traditional lithium-ion battery graphite anode is slow, especially the lithium ion insertion / deintercalation kinetics at high rates are slow; and the sodium ion has a large ionic radius, which makes it more difficult to insert / deintercalate in graphite, which will inevitably lead to a large volume expansion of the electrode material during the charge and discharge cycle, resulting in serious capacity decay at high rates. Therefore, the rate performance of traditional graphite anodes when used in sodium-ion batteries is not satisfactory, which limits the further application of sodium-ion batteries. In response to the problem of slow storage kinetics caused by the ionic radius in sodium-ion batteries, other carbon materials have been developed as anode materials for sodium-ion batteries in recent years, such as hard carbon, soft carbon, graphene, etc. Although these materials have alleviated the above problems to a certain extent, there is still a lot of room for improvement.
[0003] The development of new high-performance negative electrode materials is one of the keys to promote the development of sodium-ion batteries. With the in-depth study of negative electrode materials for sodium-ion batteries, people have come to realize that the formation and structure of the solid electrolyte interface (SEI) on the negative electrode surface are particularly important for the first-cycle coulombic efficiency, capacity, rate performance and cycle stability of sodium-ion batteries. The formation and structure of SEI are related to many factors, such as electrolyte composition, charge and discharge process, electrode material structure, etc. Among them, the surface structure of the negative electrode material will affect the decomposition behavior of the electrolyte and thus affect the formation of SEI. Therefore, regulating the surface structure of the material is a key strategy to improve the performance of sodium-ion batteries. In recent years, heteroatom modification has been proven to be one of the effective strategies to improve the formation of SEI on the negative electrode of carbon materials. The introduction of heteroatoms such as nitrogen, oxygen, and phosphorus into the carbon skeleton can change the electronegativity of the material, thereby affecting the adsorption and decomposition of electrolyte components on the surface of the material. However, most of the heteroatom modification strategies reported so far adopt a "bottom-up" design approach, that is, by designing the structure of the carbon precursor to regulate the heteroatom configuration in the product. This modification strategy is often difficult to regulate the intrinsic structure of the material; and the idea of modifying existing materials through a "post-modification" strategy is limited by the surface groups of the carbon materials, and has poor universality for carbon materials with different structures, making it difficult to apply on a large scale. Summary of the invention
[0004] The present invention provides a sodium ion battery negative electrode material and a preparation method and application thereof, so as to solve the problem of poor universality of the sodium ion battery negative electrode material modification method in the prior art.
[0005] In a first aspect, the present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps: subjecting a carbon negative electrode to surface oxidation-enriched treatment; performing a two-step thermal reaction in an inert atmosphere; wherein the first step is to perform heteroatom doping using nitrogen / sulfur-containing small molecules; the second step is to perform a calcination treatment to remove heteroatoms, and naturally cool the temperature to 25 to 30°C to obtain a carbon negative electrode material modified with surface topological defects; and physically mixing the carbon negative electrode material modified with surface topological defects with active small molecules containing heteroatoms and then performing a heat treatment in an inert atmosphere to obtain the negative electrode material for a sodium ion battery.
[0006] As a possible implementation method, the heat treatment under an inert atmosphere includes the following steps: physically mixing the carbon negative electrode material modified with surface topological defects with active heteroatom-containing small molecules, heating to 130-180°C under an inert atmosphere, and keeping warm for 6-24 hours; heating again to 200-900°C, and keeping warm for 1-20 hours; naturally cooling to 25-30°C, dispersing the obtained product in a good solvent of active heteroatom small molecules, and purifying to obtain the sodium ion battery negative electrode material.
[0007] As a possible implementation method, the carbon negative electrode is any one of hard carbon and soft carbon; and / or the nitrogen / sulfur-containing small molecules are one or a combination of melamine, urea, thiourea, cyanamide, and dicyandiamide; and / or the active heteroatom-containing small molecules are one or a combination of carbon disulfide, hydrogen sulfide, sodium thiosulfate, melamine, urea, thiourea, cyanamide, dicyandiamide, and sodium borohydride.
[0008] As a possible implementation, the surface oxidation-enriched treatment is one or a combination of oxygen plasma treatment, acid solution heat treatment, and air heat treatment; and / or, in the heteroatom doping, the mass ratio of the carbon negative electrode and the nitrogen / sulfur-containing small molecule is 1:0.5-10, the temperature condition is 600-800°C, and the duration is 1-4h; and / or, the calcination treatment, the temperature condition is 900-1400°C, the duration is 1-4h; and / or, the heat treatment, the temperature condition is 130-900°C, the treatment duration is 2-20h; and / or, the inert atmosphere is one or a combination of nitrogen, argon, and helium, and the gas flow rate of the inert atmosphere is 100-300mL·min -1 .
[0009] As a possible implementation method, the heteroatom doping has a heating rate of 2 to 5°C·min -1; and / or, the calcination treatment, the heating rate is 2 to 5 ° C. min -1 ; and / or, the heating is carried out under an inert atmosphere at a heating rate of 2 to 5 ° C. min -1 ; and / or, the heating is again increased at a rate of 2 to 5°C min -1 .
[0010] In a second aspect, the present invention provides a sodium ion battery negative electrode material prepared by the preparation method described in any possible implementation of the first aspect.
[0011] In a third aspect, the present invention provides a sodium ion battery negative electrode material prepared by the preparation method described in any possible implementation of the first aspect or an application of the sodium ion battery negative electrode material described in any possible implementation of the second aspect in a sodium ion battery.
[0012] In a fourth aspect, the present invention provides a sodium ion battery, comprising a sodium ion battery negative electrode material prepared by the preparation method described in any possible implementation of the first aspect or a sodium ion battery negative electrode material described in any possible implementation of the second aspect.
[0013] As a possible implementation method, the negative electrode material, binder, and conductive agent of the sodium ion battery are mixed in a mass ratio of 8:1:1 to prepare a slurry; the slurry is coated on a current collector to obtain a pole piece; and the pole piece is cut into an appropriate size to serve as the negative electrode pole piece of the sodium ion battery.
[0014] As a possible implementation method, the application conditions are: current density 0.05~10A·g -1 , the temperature is -20 ~ 30℃.
[0015] The present invention provides a technology for obtaining modified negative electrode materials by successively introducing defects and active small molecules on the surface of commercial sodium ion battery negative electrode materials (such as hard carbon, soft carbon, etc.). In order to conveniently describe the principle of the present invention, commercial hard carbon, melamine (nitrogen / sulfur small molecules) and sulfur powder (active heteroatom-containing small molecules) are used as raw materials as examples. First, oxygen-rich groups are introduced on the surface of commercial hard carbon by oxygen plasma pre-oxidation technology to increase the reaction sites of melamine during nitrogen atom doping. Then, melamine and hard carbon treated with surface rich oxidation are physically mixed evenly by grinding, and two-step heat treatment is carried out under the protection of an inert atmosphere to achieve low-temperature nitrogen atom doping and high-temperature nitrogen atom removal on the surface of the material, thereby obtaining hard carbon modified with surface topological defects. Subsequently, elemental sulfur and hard carbon modified with surface topological defects are physically mixed evenly by grinding, and heat treatment is carried out under the protection of an inert atmosphere, and active short-chain sulfur is modified to the surface of hard carbon by the bonding action between surface topological defects and elemental sulfur, thereby preparing hard carbon modified with surface active short-chain sulfur. The commercial hard carbon modified by this method can basically retain the original internal structure of the hard carbon (such as micropores for storing semi-metallic sodium), and the active short-chain sulfur on the surface can participate in the formation of the solid electrolyte interface, so that when it is used as the negative electrode of a sodium ion battery, it can form a more ideal solid electrolyte interface on the electrode surface and retain the original hard carbon characteristics, so that sodium ions can be transmitted in the optimized solid electrolyte interface, thereby improving the performance of the sodium ion battery, especially the rate performance, high active material loading and capacity at low temperature.
[0016] The sodium ion battery negative electrode material prepared by the present invention has significant performance advantages in the application of sodium ion batteries. The heat treatment at a relatively low temperature ensures that the internal structure of the material is not destroyed, and the active small molecules on the surface of the material participate in the formation of the solid electrolyte interface during the charge and discharge process, which helps to form a more ideal solid electrolyte interface and promote ion transport. The above structural advantages improve the ion transport kinetics of the electrode material without sacrificing the original structural advantages, which is beneficial to improving the electrochemical properties of sodium ion batteries, especially the capacity and rate performance. The present invention utilizes a topological defect construction strategy to introduce active small molecules on the surface of the carbon negative electrode material without destroying the structure of the carbon negative electrode material, significantly improving the first-cycle coulomb efficiency, rate performance and cycle stability of the sodium ion battery, especially increasing the negative electrode high active material loading and capacity at low temperatures.
[0017] The sodium ion battery negative electrode material provided by the present invention takes the commonly used commercial hard carbon negative electrode as an example. Compared with the material before modification, the modified material has an improved first-cycle Coulomb efficiency of about 5%, 5A·g -1 and 10A·g -1 The capacity retention rate is improved by about 10% at the current density, and it also has good low temperature performance (such as -20°C) and capacity at high active material loading (such as 4mg·cm -2), and has good capacity and cycle stability when used as negative electrode materials for sodium ion batteries. In addition, the present invention can also be applied to negative electrode materials of different brands and types, and can obtain modified carbon negative electrode materials with different characteristics as needed by changing the type and proportion of active small molecules without destroying the original structure of the negative electrode material; it is easy to scale up, and has good universality and scale potential.
[0018] The fast-charging carbon negative electrode material preparation strategy provided by the present invention can directly use commercial materials circulating on the market, has simple preparation steps, low material cost, and has good cost-effectiveness and scale-up potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The first cycle charge and discharge curves of the sodium ion battery negative electrode material I and the commercial hard carbon I provided in the embodiment of the present invention as the sodium ion battery negative electrode material, respectively, wherein the current density is 0.05A·g -1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 , Voltage represents voltage, and Specific capacity represents specific capacity.
[0021] Figure 2 The rate performance diagram of the sodium ion battery negative electrode material I and the commercial hard carbon I provided in the embodiment of the present invention when used as the negative electrode material of the sodium ion battery, wherein the current density is 0.05-10A·g -1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 Specific capacity means specific capacity, Cycle number means the number of cycles, and Current density means the current density.
[0022] Figure 3 The rate performance diagram of the sodium ion battery negative electrode material I and the commercial hard carbon I provided in the embodiment of the present invention when used as the negative electrode material of the sodium ion battery, wherein the current density is 0.05-10A·g -1 , temperature is 30°C, active material loading is 3.3-3.5 mg cm -2Specific capacity means specific capacity, Cycle number means the number of cycles, and Current density means the current density.
[0023] Figure 4 The rate performance diagram of the sodium ion battery negative electrode material I and the commercial hard carbon I provided in the embodiment of the present invention when used as the negative electrode material of the sodium ion battery, wherein the current density is 0.05-10A·g -1 , temperature is -20°C, active material loading is 0.5-0.8 mg cm -2 Specific capacity means specific capacity, Cycle number means the number of cycles, and Current density means the current density.
[0024] Figure 5 The first cycle charge and discharge curves of the sodium ion battery negative electrode material II and the commercial hard carbon II provided in the embodiment of the present invention as the negative electrode materials of the sodium ion battery, wherein the current density is 0.05A·g -1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 , Voltage represents voltage, and Specific capacity represents specific capacity.
[0025] Figure 6 The rate performance diagram of the sodium ion battery negative electrode material II and the commercial hard carbon II provided in the embodiment of the present invention when used as the negative electrode material of the sodium ion battery, wherein the current density is 0.05-10A·g -1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 Specific capacity means specific capacity, Cycle number means the number of cycles, and Current density means the current density.
[0026] Figure 7 The first cycle charge and discharge curves of the sodium ion battery negative electrode material III and the commercial hard carbon I provided in the embodiment of the present invention as the negative electrode materials of the sodium ion battery, wherein the current density is 0.05A·g -1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 , Voltage represents voltage, and Specific capacity represents specific capacity.
[0027] Figure 8 The rate performance diagram of the sodium ion battery negative electrode material III and the commercial hard carbon I provided in the embodiment of the present invention when used as the negative electrode material of the sodium ion battery, wherein the current density is 0.05-10A·g-1 , temperature is 30°C, active material loading is 0.5-0.8 mg cm -2 Specific capacity means specific capacity, Cycle number means the number of cycles, and Current density means the current density. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In order to solve the problem of poor universality of the modification methods of sodium ion battery negative electrode materials in the prior art, an embodiment of the present invention provides a preparation experiment of sodium ion battery negative electrode materials, and the target product is prepared under different conditions.
[0030] Furthermore, the embodiment of the present invention provides a performance test experiment of a negative electrode material for a sodium ion battery, wherein the raw material before modification and the corresponding product prepared are used as the active negative electrode material to be tested, and a half-cell is prepared. The electrochemical performance of the half-cell is tested to obtain the performance results of the corresponding active negative electrode material. It can be seen that compared with the material before modification, the modified material has a higher initial capacity, first cycle coulombic efficiency and better rate performance, and can still maintain a higher initial capacity and better rate performance under higher active material loading or low temperature conditions.
[0031] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0032] Example 1
[0033] This embodiment provides an experiment for preparing a negative electrode material for a sodium ion battery.
[0034] 1.0g of commercial hard carbon I (Kuraray, type-2) was placed in a small beaker and treated with an oxygen plasma treatment machine under the following treatment conditions: vacuum degree kept below 20Pa, treatment power 150W, treatment time 4min, and the powder was stirred evenly after each treatment. The treatment was repeated 4 times to obtain hard carbon I with rich oxidation on the surface. Hard carbon I with rich oxidation on the surface was ground and mixed evenly with 1.0g of melamine powder and placed at 200mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h. After naturally cooling to room temperature, the sample was taken out to obtain hard carbon I modified with surface topological defects.
[0035] The hard carbon I modified with topological defects on the surface was ground and mixed with elemental sulfur at a mass ratio of 1:4, placed in a small glass bottle sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 155°C and kept for 12 h, then raised to 200°C and kept for 6 h. After naturally cooling to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was placed in a vacuum oven at 40°C and dried for 12 h to obtain sodium ion battery negative electrode material I.
[0036] Example 2
[0037] This embodiment provides an experiment for preparing a negative electrode material for a sodium ion battery.
[0038] 1.0g of commercial hard carbon II (Croode, sodium ion battery hard carbon) was placed in a small beaker and treated with an oxygen plasma treatment machine under the following treatment conditions: vacuum degree kept below 20Pa, treatment power 150W, treatment time 4min, and the powder was stirred evenly after each treatment. The treatment was repeated 4 times to obtain hard carbon II with surface oxidation treatment. Hard carbon II with surface oxidation treatment was ground and mixed evenly with 1.0g of melamine powder and placed at 200mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain hard carbon II modified with surface topological defects.
[0039] The hard carbon II modified with surface topological defects and elemental sulfur were ground and mixed evenly at a mass ratio of 1:4, placed in a small glass bottle sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the -1 The heating rate was increased to 155°C and kept for 12 hours, then increased to 200°C and kept for 6 hours. After naturally cooling to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was placed in a vacuum oven at 40°C and dried for 12 hours to obtain sodium ion battery negative electrode material II.
[0040] Example 3
[0041] This embodiment provides an experiment for preparing a negative electrode material for a sodium ion battery.
[0042] 1.0g of commercial hard carbon I (Kuraray, type-2) was placed in a small beaker and treated with an oxygen plasma treatment machine under the following treatment conditions: vacuum was kept below 20Pa, treatment power was 150W, treatment time was 4min, and the powder was stirred evenly after each treatment. The treatment was repeated 4 times to obtain hard carbon I with surface oxidation treatment. The hard carbon I with surface oxidation treatment was ground and mixed evenly with 1.0g of melamine powder and placed at 200mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h. After naturally cooling to room temperature, the sample was taken out to obtain hard carbon I modified with surface topological defects.
[0043] The hard carbon I modified with topological defects on the surface was ground and mixed with elemental sulfur at a mass ratio of 1:4, placed in a small glass bottle sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the -1 The heating rate was raised to 155℃ and kept for 12h, and then the temperature was increased to 5℃·min -1 The heating rate was raised to 700°C and kept for 2 hours. The product was taken out after naturally cooling to room temperature, dispersed with carbon disulfide solution, centrifuged and placed in a vacuum oven at 40°C for 12 hours to obtain sodium ion battery negative electrode material I.
[0044] Example 4
[0045] This embodiment provides an experiment for preparing a negative electrode material for a sodium ion battery.
[0046] 1.0g of commercial soft carbon IV (Kejing, BSC-3) was placed in a small beaker and treated with an oxygen plasma treatment machine under the following treatment conditions: vacuum degree kept below 20Pa, treatment power 150W, treatment time 4min, and the powder was stirred evenly after each treatment. The treatment was repeated 4 times to obtain soft carbon IV with surface oxidation treatment. The surface oxidation treatment soft carbon IV was evenly ground with 1.0g of melamine powder and placed in a 200mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h. After naturally cooling to room temperature, the sample was taken out to obtain soft carbon IV modified with surface topological defects.
[0047] The soft carbon IV modified with surface topological defects and elemental sulfur were ground and mixed evenly at a mass ratio of 1:4, placed in a small glass bottle sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the -1The heating rate was increased to 155°C and kept for 12 hours, then increased to 200°C and kept for 6 hours. After naturally cooling to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was placed in a vacuum oven at 40°C and dried for 12 hours to obtain sodium ion battery negative electrode material IV.
[0048] Example 5
[0049] This embodiment provides an experiment for preparing a negative electrode material for a sodium ion battery.
[0050] 1.0g of commercial hard carbon I (Kuraray, type-2) was placed in a small beaker and treated with an oxygen plasma treatment machine under the following treatment conditions: vacuum degree kept below 20Pa, treatment power 150W, treatment time 4min, and the powder was stirred evenly after each treatment. The treatment was repeated 4 times to obtain hard carbon I with surface oxidation treatment. The hard carbon I with surface oxidation treatment was ground and mixed evenly with 1.0g of melamine powder and placed at 200mL min -1 In a nitrogen atmosphere, the -1 The temperature was raised to 700°C and kept for 2 h, then raised to 1050°C and kept for 2 h. After naturally cooling to room temperature, the sample was taken out to obtain hard carbon I modified with surface topological defects.
[0051] The hard carbon I modified with topological defects on the surface was ground and mixed evenly with sodium thiosulfate at a mass ratio of 1:4, placed in a small glass bottle sealed with aluminum foil, and placed at 200 mL min -1 In a nitrogen atmosphere, the -1 The heating rate was increased to 155°C and kept for 12 h, then increased to 200°C and kept for 6 h, and then naturally cooled to room temperature and taken out, the product was dispersed with water / ethanol solution, centrifuged and placed in a vacuum oven at 40°C for 12 h to obtain sodium ion battery negative electrode material I.
[0052] Example 6
[0053] This embodiment provides a performance test experiment of a negative electrode material.
[0054] A button cell, i.e. a sodium-carbon half-cell, is assembled by using a pole piece containing active negative electrode material as the positive electrode and a metal sodium sheet as the negative electrode. The purpose is to study the sodium storage performance of the active negative electrode material under the condition of sufficient sodium ions and to demonstrate its application potential in sodium-ion full batteries.
[0055] The active negative electrode material to be tested, the binder sodium carboxymethyl cellulose, and the conductive agent conductive carbon black Super P are mixed in a mass ratio of 8:1:1, and a small amount of deionized water is added, and the mixture is stirred to form a slurry with a certain viscosity; the slurry is evenly coated on the surface of the current collector copper foil using an applicator, vacuum dried at 60°C, and then cut into electrode sheets with a diameter of 12mm, and the battery is assembled in a glove box with an argon atmosphere (water and oxygen content are both less than 0.5ppm). The prepared electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, 1M NaPF6 is dissolved in diethylene glycol dimethyl ether as the electrolyte, and Whatman glass microfiber filter paper is used as the diaphragm. CR2032 button batteries are assembled in the corresponding order. The LandCT2001A battery test system is used to test the charge and discharge performance of the battery, and the charge and discharge termination range is 0.01~2.0V.
[0056] In this example, the commercial hard carbon I and the negative electrode material I of the sodium ion battery of Example 1, the commercial hard carbon II and the negative electrode material II of the sodium ion battery of Example 2, and the commercial hard carbon III and the negative electrode material III of the sodium ion battery of Example 3 were respectively used as the negative electrode materials to be tested, and the performance was measured, and the results were as follows: Figures 1 to 8 Results shown.
[0057] Depend on Figure 1 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material I of Example 1 and the commercial hard carbon I are -1 The first cycle charge and discharge tests were carried out at the current density of 86.5% and 82.5%, respectively.
[0058] Depend on Figure 2 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material I of Example 1 and the commercial hard carbon I are -1 The reversible specific capacities after stabilization at the current density are 314.4 and 287.6 mAh·g, respectively. -1 When the current density increases to 5A·g -1 and 10A·g -1 When the negative electrode material I of sodium ion battery still has 198.9 and 112.4 mAh·g -1 The reversible specific capacity of commercial hard carbon I is only 142.2 and 65.6 mAh·g -1 reversible specific capacity.
[0059] Depend on Figure 3 It can be seen that when the active substance loading is 3.3-3.5 mg cm -2When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material I of Example 1 and the commercial hard carbon I are -1 The reversible specific capacities after stabilization at the current density are 306.1 and 288.5 mAh·g -1 When the current density increases to 1A·g -1 When the negative electrode material I of sodium ion battery still has 219.5 and 109.7 mAh g -1 The reversible specific capacity of commercial hard carbon I is only 180.9 and 83.3 mAh·g -1 reversible specific capacity.
[0060] Depend on Figure 4 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is -20°C, the half-cells assembled from the sodium ion battery negative electrode material I of Example 1 and the commercial hard carbon I are -1 The reversible specific capacities after stabilization at the current density are 303.1 and 250.1 mAh·g -1 When the current density increases to 1A·g -1 and 2A·g -1 When the negative electrode material I of sodium ion battery still has 74.1 and 32 mAh·g -1 The reversible specific capacity of commercial hard carbon I is only 16.7 and 1.8 mAh·g -1 reversible specific capacity.
[0061] It can be seen that sodium-ion battery negative electrode material I has a higher initial capacity, first-cycle coulombic efficiency and better rate performance than commercial hard carbon I, and can still maintain a higher initial capacity and better rate performance under higher active material loading or low temperature conditions.
[0062] Depend on Figure 5 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material II of Example 2 and the commercial hard carbon II are -1 The first cycle charge and discharge tests were carried out at the current density of 83.3% and 78.7% respectively.
[0063] Depend on Figure 6 It can be seen that the half-cells assembled from the sodium ion battery negative electrode material II of Example 2 and the commercial hard carbon II are at 0.05 A·g -1 The reversible specific capacities after stabilization at the current density are 308.7 and 276.6 mAh·g -1 When the current density increases to 5A·g -1 and 10A·g-1 When the negative electrode material II of sodium ion battery still has 138.8 and 66.9 mAh g -1 The reversible specific capacity of commercial hard carbon II is only 44.7 and 19.7 mAh·g -1 reversible specific capacity.
[0064] It can be seen that sodium ion battery negative electrode material II has higher initial capacity, first-cycle coulombic efficiency and better rate performance than commercial hard carbon II.
[0065] Depend on Figure 7 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material III of Example 3 and the commercial hard carbon I are -1 The first cycle charge and discharge tests were carried out at the current density of 800 nm and 850 nm, and the first cycle coulombic efficiency was 88.1% and 82.5% respectively.
[0066] Depend on Figure 8 It can be seen that when the active substance loading is 0.5-0.8 mg cm -2 When the test temperature is 30°C, the half-cells assembled from the sodium ion battery negative electrode material III of Example 3 and the commercial hard carbon I are -1 The reversible specific capacities after stabilization at the current density are 328.1 and 287.6 mAh·g, respectively. -1 When the current density increases to 5A·g -1 and 10A·g -1 When the negative electrode material III of sodium ion battery is still 208.5 and 115.6 mAh g -1 The reversible specific capacity of commercial hard carbon I is only 142.2 and 65.6 mAh·g -1 reversible specific capacity.
[0067] It can be seen that sodium-ion battery negative electrode material III has higher initial capacity, first-cycle coulombic efficiency and better rate performance than commercial hard carbon I.
[0068] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0069] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: The carbon negative electrode is subjected to surface oxidation enrichment treatment; A two-step thermal reaction is carried out in an inert atmosphere; the first step is to use nitrogen / sulfur small molecules for heteroatom doping; the second step is to perform calcination treatment to remove heteroatoms, and then naturally cool to 25-30°C to obtain a carbon negative electrode material with surface topological defects modified; The surface topological defect-modified carbon negative electrode material is physically mixed with active heteroatom-containing small molecules and then heat-treated under an inert atmosphere to obtain the sodium ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that: The heat treatment under an inert atmosphere comprises the following steps: The surface topological defect-modified carbon negative electrode material is physically mixed with active heteroatom-containing small molecules, heated to 130-180° C. in an inert atmosphere, and kept warm for 6-24 hours; heated again to 200-900° C., and kept warm for 1-20 hours; naturally cooled to 25-30° C., the obtained product is dispersed in a good solvent of active heteroatom small molecules, and purified to obtain the sodium ion battery negative electrode material.
3. The preparation method according to claim 1, characterized in that: The carbon negative electrode is any one of hard carbon and soft carbon; And / or, the nitrogen / sulfur-containing small molecule is one or a combination of melamine, urea, thiourea, cyanamide, and dicyandiamide; And / or, the active small molecule containing heteroatoms is one or a combination of carbon disulfide, hydrogen sulfide, sodium thiosulfate, melamine, urea, thiourea, cyanamide, dicyandiamide, and sodium borohydride.
4. The preparation method according to claim 1, characterized in that: The surface oxidation treatment is one or a combination of oxygen plasma treatment, acid solution heat treatment, and air heat treatment; And / or, in the heteroatom doping, the mass ratio of the carbon negative electrode to the nitrogen / sulfur-containing small molecule is 1:0.5-10, the temperature condition is 600-800° C., and the duration is 1-4 hours; And / or, the calcination treatment is carried out at a temperature of 900 to 1400° C. and for a time of 1 to 4 hours; And / or, the heat treatment has a temperature condition of 130-900° C. and a treatment time of 2-20 hours; And / or, the inert atmosphere is one or a combination of nitrogen, argon, helium, and the gas flow rate of the inert atmosphere is 100 to 300 mL min -1 .
5. The preparation method according to any one of claims 1 to 2, characterized in that: The heteroatom doping, the heating rate is 2 to 5 ° C. min -1 ; And / or, the calcination treatment has a heating rate of 2 to 5°C·min -1 ; And / or, the heating is carried out under an inert atmosphere at a heating rate of 2 to 5°C·min -1 ; And / or, the heating is again increased at a rate of 2 to 5°C·min -1 .
6. A sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 5 or the sodium ion battery negative electrode material according to claim 6 in a sodium ion battery.
8. A sodium ion battery, characterized in that: The invention comprises a sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 5 or a sodium ion battery negative electrode material according to claim 6.
9. The sodium ion battery according to claim 8, characterized in that: The sodium ion battery negative electrode material, the binder, and the conductive agent are mixed in a mass ratio of 8:1:1 to prepare a slurry; Applying the slurry on a current collector to obtain a pole piece; The electrode sheet is cut into an appropriate size to serve as the negative electrode sheet of the sodium ion battery.
10. The sodium ion battery according to claim 8, characterized in that: Its application conditions are: current density 0.05~10A·g -1 , the temperature is -20 ~ 30℃.
Citation Information
Patent Citations
Heteroatom-doped porous hard carbon negative electrode material and preparation method and application thereof
CN118289737A
Sodium-ion battery biomass hard carbon negative electrode material based on heteroatom modification and preparation method thereof
CN118561261A